FROM POLICY FRAMEWORKS TO CLASSROOMS: EFL CHALLENGES IN INDONESIA - Novi Indriyani (Acceleration: Multidisciplinary Research Journal, 2025)
This article explores the multifaceted challenges facing English as a Foreign Language (EFL) education in Indonesia, focusing on the interplay between national policy, curriculum implementation, and classroom practices. Employing a systematic literature review (SLR) methodology, this study synthesizes findings from academic publications, government reports, and international research from 2004 to 2024. The analysis reveals persistent issues, including policy-practice gaps, limited teacher training, resource disparities, and insufficient attention to local contexts in curriculum development. Additionally, classroom-level obstacles such as mixed-ability learners, low motivation, and lack of authentic materials hinder effective language instruction. The study emphasizes the need for adaptive pedagogical approaches, continuous professional development, and a more localized curriculum design. These findings contribute to a deeper understanding of EFL complexities in Indonesia and offer insights for policymakers, educators, and researchers committed to enhancing English education across diverse regions.